PENGARUH PERENDAMAN DALAM AIR SAWAH TERHADAP PENURUNAN BIOMASSA DAN PERUBAHAN STRUKTUR ANATOMI KAPAS (Gossypium sp) DAN JERAMI PADI (Oryza sativa L) - Eni Yuspika; Munifatul Izzati; Sri Haryanti (Jurnal Akademika Biologi, 2013)
Cellulose is a constituent component of plant cell walls. Cellulose is protected by lignin and hemicellulose, it is difficult to degrade so it is necessary to elaborate pretreatment component. Pretreatment is a crucial step to creation of lignocellulose-based bioethanol. Pretreatment serves to break up and remove lignin and damage to the crystalline structure of cellulose that makes unraveling cellulose into glucose. This study aims to determine the decrease in biomass and changes of anatomical structures on cotton and rice straw soaked in rice water. This research was conducted in the Laboratory of Biological Structure and Function of Plant Biology UNDIP FSM. The design used was using T-test analysis and descriptive data with the two treatments are soaking in distilled water and water field. Parameters observed decrease of biomass and structure changes ( macroscopic and microscopic). The results showed soaking rice in water significantly affect biomass decreased as much as 27.5% cotton and rice straw as much as 31.36%. Changes in the anatomical structure of the cotton that damages both sides of the cell wall, the lumen crushed and partially soluble, while rice straw damage on one side of the cell wall and partially soluble cell contents.Key words: biomass, anatomical structure, cotton, rice straw, rice water